Pengaruh Organizational Learning, Organizational Commitment dan Job Satisfaction Terhadap Employee Performance di Jakarta - Rahadian Mohamad; M. Tony Nawawi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This research is focusing on three variables of Organizational Learning, Organizational Commitment and Job Satisfaction, and its effects on Employee Performance. Total of 90 employees who work in General Service Division of Bank BTPN Jakarta are selected as samples for this research. The methods used are Quantitative Research, in which all the samples are required to answer an online questionnaire that the researcher sent. Then, the results of the questionnaire were analyzed with PLS-SEM methods using analytical software SmartPLS 3. The results showed that (1) Organizational Learning has a positive and significant effect on Employee Performance, (2) Organizational Commitment has a positive and significant effect on Employee Performance, and (3) Job Satisfaction has a positive and significant effect on Employee Performance. Dalam penelitian ini berfokus pada tiga variabel, yaitu Organizational Learning, Organizational Commitment dan Job Satisfaction, dan pengaruhnya terhadap Employee Performance. Penelitian ini dilakukan terhadap 90 responden yang bekerja pada divisi General Service di Kantor Pusat Bank BTPN Jakarta. Metode penelitian yang digunakan adalah metode kuantitatif, dimana responden akan menjawab kuesioner berbasis online yang dikirimkan oleh peneliti. Kemudian data yang diperoleh diolah dengan metode PLS-SEM menggunakan software pengolahan data SmartPLS 3. Hasil penelitian menunjukkan bahwa (1) Organizational Learning mempunyai pengaruh yang positif dan signifikan terhadap Employee Performance, (2) Organizational Commitment mempunyai pengaruh yang positif dan signifikan terhadap Employee Performance, dan (3) Job Satisfaction mempunyai pengaruh yang positif dan signifikan terhadap Employee Performance.